Estudo fitoquímico e avaliação do potencial biológico de Senega pulchella e Senega trichosperma - Silva, Syntia Meneses (2025)
The use of plants for therapeutic purposes is one of the oldest medicinal practices known to humanity, and vegetal resources remain strategic sources of bioactive molecules with pharmacological potential. This study aimed to investigate the phytochemical profile and evaluate the biological potential of Senega trichosperma and Senega pulchella (Polygalaceae), collected on the campuses of the Universidade Estadual de Feira de Santana (UEFS) and the Universidade Federal de Santa Catarina (UFSC), respectively. After drying, the aerial parts and roots were subjected to different extraction methods: methanolic maceration (MM), ethanolic maceration (ME), Soxhlet extraction (SOX), and ultrasound-assisted extraction (ULT). The methanolic maceration extracts were further partitioned using a liquid–liquid fractionation system with solvents of increasing polarity: hexane, chloroform, and ethyl acetate. HPLC-DAD analyses revealed similar chromatographic profiles among the extraction methods, highlighting the consistent presence of two compounds (salicylic acid and 1,5-dihydroxy-2,3- dimethoxyxanthone) across all samples. Extraction yields ranged from 10.8% to 27%, with the highest values observed for Soxhlet methanolic extraction. The fractions obtained from partitioning were submitted to successive chromatographic processes (CC and MPLC), which enabled the isolation of metabolites belonging to the xanthone and coumarin classes. Among the isolated xanthones, 1,5-dihydroxy-6’,6’-dimethylpyrano [2’,3’:3,2] -xanthone (6- desoxijacareubin) and 1,5-dihydroxy-2,3-dimethoxyxanthone were identified. Within the coumarins, 2,2-dimethylpyranocoumarin (Seselin) and 8-(3-methyl-2-butenyl) benzopyran-2- one (Osthol) were isolated. Structural characterization was confirmed by ¹H and ¹³C NMR (including DEPT, HMQC, and HMBC), IR, and MS analyses. In the biological assays, crude extracts and fractions exhibited relevant levels of phenolics (up to 106.8 ± 4.56 mg GAE·g⁻¹) and flavonoids (up to 58.6 ± 0.63 mg QE·g⁻¹), associated with antioxidant activity (IC₅₀ of 1.42 ± 0.119 mg·mL⁻¹ for DPPH; IC₅₀ of 0.200 ± 0.0 mg·mL⁻¹ for ABTS; and IC₅₀ of 0.267 ± 0.04 mg·mL⁻¹ for the β-carotene assay). Antimicrobial evaluation demonstrated activity against Gram-positive bacteria and yeast-like fungi, with MIC values of 1024 μg/mL for SPMM and 512 μg/mL for 6-desoxijacareubin and Osthol. Anticholinesterase activity was prominent, with 56.78% AChE inhibition for SPSOX and 48.65% BuChE inhibition for SPULT. Additionally, 6-desoxijacareubin yielded IC₅₀ values of 69.5 µM for AChE and 47.3 µM for BuChE, while Osthol exhibited IC₅₀ values of 45.0 µM and 298.5 µM for AChE and BuChE, respectively, results corroborated by in silico molecular docking analyses that revealed stable interactions with the catalytic sites of the enzymes. In cytotoxicity assays, SPSOX, SPMM, and SPULT showed higher activity against the K562 cell line (IC₅₀ = 240.8, 271.4, and 251.4 µg/mL, respectively), with selectivity indices greater than 2 compared to McCoy fibroblasts. Regarding anti-leishmanial activity, the isolated compounds inhibited the LbSODB2 enzyme from Leishmania braziliensis, and the thermal shift responses observed for Osthol and 6- desoxijacareubin suggested potential destabilization of the protein structure. Overall, the results highlight S. trichosperma and S. pulchella as promising sources of bioactive metabolites with multiple pharmacological properties and chemotaxonomic relevance, contributing to the rational and sustainable use of Brazilian biodiversity.